Primary Large Cell Neuroendocrine Carcinoma of Buccal Mucosa: A Report of a Case at an Unusual Location - Kadkol, Girish Anandrao; Phadke, Madhura Devdatta; Nisar, Zeba; Pol, Jaydeep Nilkanthrao (Annals of Pathology and Laboratory Medicine, 2018)
Neuroendocrine carcinoma is a poorly differentiated carcinoma that usually occurs in the lung. Large cell neuroendocrine carcinoma is a Non-small cell lung carcinoma that shows histological features of neuroendocrine morphology (including rosettes and peripheral palisading) and expresses immunohistochemical neuroendocrine markers. Oral cavity is an exceedingly rare site for primary Neuroendocrine Carcinoma. This case report describes Primary Large Cell Neuroendocrine Carcinoma (LCNEC) of buccal mucosa and lower gingiva in a 65 years old male. To the best of the author’s knowledge this is the third case of intraoral LCNEC & second case with LCNEC in buccal mucosa to date in English literature. Thus far, only a small number of cases of intraoral mucosal Neuroendocrine carcinoma have been reported and no definitive standard treatment strategy has been determined.